Proyecto de creación de una microempresa de diseño y comercialización de camisetas personalizadas via web - Hidalgo Zambrano, Ma. Gabriela (2010)
There is a need of many people in the city of Guayaquil that many of them are inclined to buy T-shirts designed, there are similar models, where people like to have their own design to their taste and preference, and above all, be a leader in continuous interaction with the fashion trend, and there is not an online store that meets your needs tastes and preferences. CamisetasPeluconas.com is an online store that will be created for users with this election, to meet consumer needs by providing the convenience of delivering shopping to home, without needing to travel to place of purchase. Our product is a symbol of modern times worldwide since 50. Our product is variable, not only by the different colors and illustrations, but the different ways they are buying. Available in different materials, screen printing many photos, drawings and illustrations of messages, which reinforces the festive atmosphere at the garment. The objective of this field is to produce custom t-shirts to offer the ease and convenience to the customer by developing its original design, a leader in continuous interaction with the trends of fashion with technology.